In House Training Untuk Meningkatkan Kompetensi Guru Menyusun RPP di SDN 195/X Sungai Jambat Semester Ganjil Tahun Ajaran 2021/2022 - Zainal Zainal (Journal on Education, 2023)
This study aims to obtain information and discuss in-house training in increasing teacher competency in compiling lesson plans at SDN 195/X Sungai Jambat in the odd semester of the 2021/2022 academic year. This type of research is school action research (PTS) conducted by the principal at SDN 195/X Sungai Jambat in the odd semester of the 2021/2022 school year with 8 teacher subjects. Data collection techniques using observation, field notes and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion, it can be concluded that there is an increase in teacher competence in preparing lesson plans at SDN 195/X Sungai Jambat through in-house training (IHT) which can be seen from the percentage of completeness from cycle I to cycle II